Transforming Imaginative Narrative Reading Learning by Literacy Cloud-Assisted PQ4R Model: A Case Study of 2nd-grade Students - Widiyaningsih, Puput; Latifah, Nur; Obi Nja, Cecilia (International Journal of Learning Reformation in Elementary Education, 2025)
This study explores how the PQ4R learning method (Preview, Question, Read, Reflect, Recite, and Review) and digital media by Literacy Cloud can help second-grade students better at reading imaginative stories. This study used a pretest-posttest control group design using a quasi-experimental method. There were two groups: an experimental group and a control group. The sample consisted of two classes with 26 students in each class, so there were 52 students in total. The researchers tested imaginative narrative reading skills before and after the learning activities to collect data. The experimental group learnt utilizing the PQ4R method, supported by Literacy Cloud, while the control group used the usual learning method. After analyzing the data, the results showed that both groups enhanced their average reading scores. The experimental group's average score improved by 5.15 to 8.00, while the control group's score went up by 4.85 to 6.27. A paired t-test showed a significant difference between the scores before and after learning in both groups (p = 0.000). An independent t-test also showed a clear difference between the post-test scores of the two groups (p = 0.000), with the experimental group scoring 1.731 points higher on average than the control group. Based on the results, it can be concluded that the PQ4R learning model, supported by Literacy Cloud, is effective in helping second-grade elementary students improve their ability to read imaginative stories.